The Impact of GDP, Inflation, Exchange Rate, and IA-CEPA on the Indonesia-Australia Trade Deficit - Aulia, Fitrotul Anindita; Kuncoro, Trian Gigih (Universitas Muhammadiyah Surakarta, 2024)
Purpose: Information Globalization has increased international trade cooperation, including the growing ties between Indonesia and Australia through the IA-CEPA agreement. However, despite Australia being a strategic partner, it contributes significantly to Indonesia's trade deficit. This study aims to identify the factors driving the trade deficit between Indonesia and Australia. It analyzes the impact of the IA-CEPA agreement and the macroeconomic variables of both countries. These variables include Indonesia's GDP, Australia's GDP, Indonesia's inflation, Australia's inflation, and the Rupiah exchange rate. Methodology: This research adopts a quantitative approach, using data spanning the period from 1991 to 2023, sourced from the International Trade Centre, International Monetary Fund, and Organisation for Economic Cooperation and Development. To analyze these variables' short-term and long-term effects, the study employs the Error Correction Model (ECM) method using Eviews 9. Results: The results indicate that, in both the short and long term, Australia's GDP has a significantly positive effect on Indonesia's trade balance. Conversely, Indonesia's GDP and inflation significantly negatively impact in the long term. Australia's inflation is found to have a significant negative impact in the short term. Additionally, the IA-CEPA agreement has a significant negative effect in both the short and long term. Meanwhile, the exchange rate does not show a significant influence in either period. Applications/Originality/Value Indonesia must take strategic steps to improve bilateral trade performance with Australia by developing potential sectors, controlling inflation, and strengthening the competitiveness of local industries.